Trypanosoma vivax in Glossina palpalis gambiensis do not appear to affect feeding behaviour, longevity or reproductive performance of the vector - Makumi, J.N.; Moloo, S.K. (Wiley, 1991)
Abstract. Feeding behaviour of Glossina palpalis gambiensis Vanderplank infected with Trypanosoma vivax Ziemann was studied and compared with that of uninfected control tsetse. The parameters measured were: total number of probes into the ear‐skin of rabbits; rate of bloodmeal engorgement; weight of freshly ingested blood; survival; and mean weight of pupae. The results showed that the rosettes of T. vivax parasites in the labrum did not interfere with the feeding behaviour of the vectors. Furthermore, mean survival of T.vivax‐infected males was significantly higher (82.2±4.2 days) compared with that of uninfected ones (70.5±3.1 days). However, with the female tsetse, mean survival of those infected was lower (98.8±4.0 days) compared to the uninfected controls (102.2±5.6days), but the difference was not significant. A few infected males and females lived a little longer than the uninfected ones. Fecundity of the female tsetse remained unaffected by the infection, and furthermore the mean weight of pupae from the infected females was not significantly different from that of pupae from the uninfected control group. Thus the physiology of pregnant female tsetse in terms of nourishment of intra‐uterine larva was unaffected by T. vivax infection.Two successive probes into the skin of two different goats followed by feeding on a third goat by each of four infected tsetse resulted in successful transmission of the infection to eleven out of twelve goats. Thus probing alone into the skin of this host can result in the transmission of T. vivax infection.